Implikasi Hukum Deepfake: Telaah terhadap UU ITE dan UU PDP - Rafi Satrya Arvitto (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the regulation of deepfake technology usage within the legal framework of Indonesia, particularly concerning the Information and Electronic Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP). The main focus of this research is to identify whether existing regulations are sufficiently effective in addressing the threats posed by the misuse of deepfake technology and to assess the extent to which legal gaps affect the protection of victims. Methodology: This research employs a normative juridical approach with a statute-based method. The data used in this study includes primary and secondary legal materials, including relevant regulations and literature discussing deepfake technology and its impact on the law. Results: The research findings reveal that while UU ITE and UU PDP regulate data falsification and personal data protection in general, they do not specifically address the use of deepfake technology. This has resulted in a legal gap that causes uncertainty in handling deepfake cases in Indonesia. As a consequence, many abuses of this technology cannot be clearly addressed under existing regulations. Limitations: This study is limited to an analysis of existing regulations in Indonesia and does not include a comparative study with regulations in other countries. Furthermore, the research does not cover technical solutions related to deepfake detection, which could be part of a preventive approach. Contribution: This research contributes to understanding the shortcomings of regulations concerning deepfake technology in Indonesia and emphasizes the need for updates or additions to the legal framework to address these specific crimes. The study also provides a foundation for the development of more effective legal policies to tackle digital threats, particularly in relation to personal data protection and the misuse of AI technology.